ANALISA KINERJA KEUANGAN DENGAN ANALISA PROFITABILITAS DAN SOLVABILITAS PADA PT BANK SYARIAH MUAMALAT INDONESIA TAHUN 2006-2007 (Riset Manajemen & Akuntansi, 2011)
Banking syariah growth in Indonesia recently becoming mount and glorious progressively. One of the the Moslem law banking is PT BANK SYARIAH MUAMALAT INDONESIA Tbk. As first banking syariah is in Indonesia expected by this Bank will progressively expand in the centre of the hoisterous of growth of Moslem law banking in Indonesia. ThatS motivation why writer interest to know financial statement at the bank. Obyektif of this writing is wishing to know PT BANK SYARIAH MUAMALAT INDONESI Tbk performance or progress with profitability and solvability analysis. From Financial Statement PT BANK SYARIAH MUAMALAT INDONESIA Tbk in the year 2006 and 2007, obtained the following result : For the analysis of ROA profitability experience of improvement although in general the result is small, for the ROE there is improvement, operating expenses ratio (OCR) progressively mount to burden there is degradation of performance, from net profit margin ( NPM) also experience of degradation. For the analysis of solvability from CAR facet experience of degradation, from debt equity ratio ( DET) experience of improvement burden degradation of performance, from Long To Debt to Asset (LTDA) experience of degradation mean there is make-up of performance. Become as a whole PT BANK SYARIAH INDONESIA Tbk growth in the year 2006-2007 not yet shown the make-up of performance is such as those which expected. To the future is it expected by the bank can improve its performance so that can vie with other Moslem law banking emerging is latter Banking Moslem law growth in Indonesia recently becoming mount and glorious progressively. One of the the Moslem law banking is PT BANK SYARIAH MUAMALAT INDONESIA Tbk. As first Moslem law is in Indonesia expected by this Bank will progressively expand in the centre of the hoisterous of growth of Moslem law banking in Indonesia. ThatS motivation why writer interest to know financial statement at the bank